2021
DOI: 10.1038/s41598-021-83906-6
|View full text |Cite
|
Sign up to set email alerts
|

AT1 receptor blocker, but not an ACE inhibitor, prevents kidneys from hypoperfusion during congestive heart failure in normotensive and hypertensive rats

Abstract: To provide novel insights into the pathogenesis of heart failure-induced renal dysfunction, we compared the effects of ACE inhibitor (ACEi) and AT1 receptor blocker (ARB) on systemic and kidney hemodynamics during heart failure in normotensive HanSD and hypertensive transgenic (TGR) rats. High-output heart failure was induced by creating an aorto-caval fistula (ACF). After five weeks, rats were either left untreated or treatment with ACEi or ARB was started for 15 weeks. Subsequently, echocardiographic, renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 57 publications
5
32
3
Order By: Relevance
“…Given the recent discovery that elevated ANG 1-7/ANG II ratio predicts a beneficial outcome of HF [66], our present findings are significant in that they suggest that the initial compensatory response in the ACF-induced model of HF in TGR consists of the activation of the vasodilatory/natriuretic axis of the RAS, which may override the effects of activation of the vasoconstrictor/sodium retaining axis. At first glance, these findings seem to diverge from our previous studies in ACF TGR [37,51,67], in which we observed that plasma and kidney ANG II, aldosterone, and NE levels are much higher than in their sham-operated counterparts. Thus, in this HF model, the vasoconstrictor/sodium retaining axis of the RAS along with the sympathorenal axis appeared to be activated.…”
Section: Activity Of the Neurohormonal Systems In Acf-induced Heart Failurecontrasting
confidence: 99%
See 4 more Smart Citations
“…Given the recent discovery that elevated ANG 1-7/ANG II ratio predicts a beneficial outcome of HF [66], our present findings are significant in that they suggest that the initial compensatory response in the ACF-induced model of HF in TGR consists of the activation of the vasodilatory/natriuretic axis of the RAS, which may override the effects of activation of the vasoconstrictor/sodium retaining axis. At first glance, these findings seem to diverge from our previous studies in ACF TGR [37,51,67], in which we observed that plasma and kidney ANG II, aldosterone, and NE levels are much higher than in their sham-operated counterparts. Thus, in this HF model, the vasoconstrictor/sodium retaining axis of the RAS along with the sympathorenal axis appeared to be activated.…”
Section: Activity Of the Neurohormonal Systems In Acf-induced Heart Failurecontrasting
confidence: 99%
“…Likewise, the beneficial effects of ACEi treatment on the survival rate accord with our line of reasoning: it is generally agreed that even if activation of the vasoconstrictor/sodium retaining axis of the RAS may be initially beneficial, the long-lasting actions might be detrimental and importantly contribute to the progression of HF to the fatal end [6,14,15,63,64]. In addition, in previous studies, we clearly demonstrated that the activity of circulating and intrarenal vasoconstrictor/sodium retaining axis of the RAS is markedly increased in ACF TGR in the advanced HF phase [37,51], and that blockade of this axis by ACEi dramatically improves survival rate [30,37,41].…”
Section: Effects Of the Treatment Regimens On The Survival Ratesupporting
confidence: 86%
See 3 more Smart Citations